Multicultural component in philosophical and pedagogical discourses (Pedagogy of Higher and Secondary Education, 2012)
Furt D. V. Multicultural component in philosophical and pedagogical discourses.The article describes the ideas formation process of polycultural education; throws the light on the philosophers’ and educators’ views concerning the principles of polyculture and relationships between different cultures.
Keywords: polycultural education; culture; cultural relativism; polycultural principle; polyculture